2012
DOI: 10.1177/1352458512463765
|View full text |Cite
|
Sign up to set email alerts
|

Heat sensitive persons with multiple sclerosis are more tolerant to resistance exercise than to endurance exercise

Abstract: An exercise-induced increase in C(temp) is associated with increased number and severity of perceived symptoms in HS persons with MS. Based on these findings it is expected that HS persons with MS do tolerate RE better than EE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…26 Most of these studies include both RRMS and progressive disease, so whether those with progressive multiple sclerosis, or severe disability, also benefit remains uncertain. Encouragingly, evidence from recent small-scale exercise studies of people with progressive multiple sclerosis, with moderate and severe disability, suggests that endurance training can improve aerobic capacity, 25,76 leading to an increase in walking distance. 25 Low dropout rates and good levels of adherence also provide cautious optimism that this intervention is feasible and acceptable in those with progressive disease.…”
Section: Reduced Cardiovascular Fitnessmentioning
confidence: 99%
“…26 Most of these studies include both RRMS and progressive disease, so whether those with progressive multiple sclerosis, or severe disability, also benefit remains uncertain. Encouragingly, evidence from recent small-scale exercise studies of people with progressive multiple sclerosis, with moderate and severe disability, suggests that endurance training can improve aerobic capacity, 25,76 leading to an increase in walking distance. 25 Low dropout rates and good levels of adherence also provide cautious optimism that this intervention is feasible and acceptable in those with progressive disease.…”
Section: Reduced Cardiovascular Fitnessmentioning
confidence: 99%
“…Impaired regulation of body temperature is a major barrier to exercise for people living with MS [19,20]. In a cross sectional study, heat sensitive individuals with MS had simultaneous increase in core temperature and worsening of MS symptoms during aerobic exercise, when compared to resisted exercise [21]. Our previous research showed that cooling the exercise environment to 16°C, mitigated exercise-induced losses in central drive among people with MS who reported having heat sensitivity [22].…”
Section: Introductionmentioning
confidence: 94%
“…Twelve patients with multiple sclerosis (MS) were selected to participate in this study. Sample size of the population was based on sample sizes of similar studies in patients with MS in which significant effects were found (Grahn et al, 2008;Reynolds et al, 2011;Skjerbaek et al, 2013;White et al, 2000). Patients were included regardless of age and gender.…”
Section: Participantsmentioning
confidence: 99%